Business Intelligence Analysis in HRIS Monitoring Dashboards using Power BI - Dearniwati, Erma; Suprihadi, Untung; Alexander, Onki (Syntax Corporation, 2024)
This study aims to design and develop an information dashboard to assist PT. Samudra Dyan Praga in managing human resources (HR) and budgeting in exhibition activities. The research method used is a web-based information system design approach, which involves the stages of design, development, and testing of a dashboard to monitor and report on labor needs in real time. The result of this research is the creation of a dashboard that provides information on the number of workers needed, job specifications, and the budget required for each ongoing exhibition project. This dashboard can also display data accurately and in a timely manner to facilitate decision-making by management. The conclusion of this study is that the implementation of an information dashboard can improve the efficiency and effectiveness of HR management and reduce unplanned cost overruns in exhibition activities. The implication of this research is that the company can more easily monitor labor needs and evaluate budgets, which in turn supports strategic decision-making in the company’s operations, particularly in HR management and cost control.